Electrodynamic analysis method of a photon crystal consisting of perfectly conducting hollow 3d cylinders. Issue 7 (3rd May 2022) - Donets, I.V.; Lerer, A.M.; Li, Zi Meng; Sledkov, V.A.; Tsvetkovskaya, S.M.
Abstract : A strict, effective electrodynamic method for analysing three-dimensional periodic lattices made of hollow metal cylinders with walls of finite thickness has been developed. The software developed has high accuracy and short computing time. It is used to find the dependences of the delays of eigenwaves on dimensions of the lattices and cylinders (length, diameter, wall thickness) for different directions of propagation and polarization of the wave. Analysis of rectangular and hexagonal lattices is performed.